Lexeme Go (Hunt for the word) / Azlan Abdul Rahman…[et al.] - Abdul Rahman, Azlan; Hamid, Suhardi; Aminuddin, Adnan; Md Saleh, Mohd Nor Azam; Shahwalludin, Syahrini (Universiti Teknologi MARA, Kedah, 2018)
Lexeme Go! is a language-based game meant for learning via fun approach. This innovation is a language-based game which emphasizes the realm of 9 categories of parts of speech. Lexeme-Go! asserts on the cognitive and psychomotor attributes of the participants and revving their physical endurance. This innovation will enhance an interactive and attractive communication, electronically, it is operated with less manpower dependency and paper-free.